EU framework for foreign direct investment control - Bourgeois, Jacques H. J., 1936- (European monographs ;, 2020)
Companies engaged in FDI or financial services will appreciate the detailed analysis of issues raised by this new EU policy instrument. This book is supposed to improve the practitioners? understanding of the EU regulatory layer now coming on top of FDI screening at the Member State level. Practitioners active in competition law, particularly mergers and acquisitions, will welcome this clear commentary and analysis of a crucial component of EU policy in the related areas of trade and investment, and policymakers will be encouraged to consider whether further regulatory changes are called for.